Musculoskeletal pain as the effect of internal compensatory mechanisms on structural and functional changes in body build and posture in elite Polish sitting volleyball players - Zwierzchowska, A.; Gawel, E.; Celebanska, D.; Rosolek, B. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background With the dynamic development of professional Paralympic sport, the prevalence of musculoskeletal pain and structural and/or functional disturbances in Para athletes constantly increases. The aim of the study was to evaluate the impact of internal compensatory mechanisms on selected aspects of body structure and function in elite sitting volleyball players.